A Comparative Numerical Study between Minorant Functions and Line Search Methods in Penalty Methods for Linear Optimization - Leulmi, Assma (Engineering, Technology & Applied Science Research, 2023)
The aim of this paper is to present a comparative numerical study between the minorant functions and line search methods in computing the step size in the penalty method for linear optimization. The minorant functions were confirmed by many interesting numerical experimentations to be more beneficial than the classical line search methods.